Michał Kalecki: An Intellectual Biography Volume II: By Intellect Alone 1939-1970 - Toporowski, Jan (Palgrave Studies in the History of Economic Thought,, 2018)
This volume of intellectual biography records the work of Michał Kalecki's maturity: his work on monetary economics and the theory of profits; his work on the problems of socialism and developing countries; and the extension of his theory of capitalism to define his work in relation to Keynes and previous political economic principles. Kalecki had, by 1939, laid out the essential elements of his theory of the business cycle in capitalism. This book begins at Oxford where, at the Institute of Statistics, he worked on the economic planning and financing of World War Two, as well as extending and detailing the particulars of his theory and examining the conditions for full employment in the post-War international monetary and financial system. Kalecki would then work for the United Nations on full employment, inflation, and developing countries. He departed from the United Nations in 1955, and returned to Poland to extend two new directions of his ideas - on the economics of developing countries and his theory of growth in the socialist economy, alongside further work on business cycles. This book is essential reading for all those who want to understand Kalecki's lasting contribution to economic theory and policy.